Share Price and Trading Volume Reactions to Lockup Expiration in Malaysian IPOs - Mohamed-Arshad, Shamsul Bahrain; Taufil-Mohd, Kamarun Nisham; Ahmad-Zaluki, Nurwati Ashikkin (International Journal of Economics and Financial Issues, 2016)
This paper examines the market reaction at the expiration of IPO lockup on share prices and trading volume. The sample consists of 292 IPOs listed on Bursa Malaysia between May 2003 and December 2012. IPO lockup in Malaysia is mandatory as opposed to voluntary where it is negotiated between firms and underwriters. Using the market model event study method, the result shows a significant negative abnormal return at the expiration of the lockup period. Thus, the study provides evidence that contradicts the semi-strong form of the Efficient Market Hypothesis (EMH). According to EMH, the expiration of the lockup period which is public knowledge should not be accompanied with a significant abnormal return. In addition, the study also shows the existence of higher abnormal trading volume at lockup expiration. Keywords: Efficient Market, Event Study, IPO, Lockup JEL Classification: G14